A MAN UNDER THE PRECIPICE OF INDUSTRIAL AND INFORMATION EXISTENCE - Yatsuk, N. Ye. (Anthropological Measurements of Philosophical Research, 2012)
The author contemplates post-modern concepts of contemporary anthropological processes and makes a conclusion about the vitality of building an anthropological model with the key concept of way-out.